27. The Effectiveness Of High Protein Nutrient To The Post Sectio Caesarea Healing Process - Darmawati Darmawati; Cut Husna; Aida Fitri; Dahrul Munira (Jurnal Medika Veterinaria, 2019)
The prevalence of cesarean section (SC) continues to increase along with the quality of technical facilities improvement. Failure to recover the surgical wounds after cesarean section is one of the possible SC complications that should be taken seriously. Proper nutrition greatly affect to wound healing. This study aims to found the effectiveness of high protein nutrients intake for post SC wound healing process at dr. Zainoel Abidin Hospital Banda Aceh. Design: This study is an experimental research with post test for intervention and control group design and using purposive sampling with the observation format as the measuring instrument. A total of 30 mother with post sectio caesarea participated in this study. There was a significant difference between post-SC wound healing in the intervention group (46.7%) compare to the control group (6.7%) (0.000). The mean of wound healing in the proliferation phase in the intervention group was faster than the control group respectively (10.47; 7.93). The hospital should provide information and evaluate high protein intake especially in post-SC patients during the treatment time, so that the patient is able to apply the information until they are going back home.